ANALISIS INTEGRASI CERITA RAKYAT DAERAH JAMBI "LEBUNG PENDAM" KE DALAM BENTUK SENI PERTUNJUKAN DI SDN 14/I SUNGAI BAUNG - Sobrini Fauziah; Siti Marwiyah; Anas Tasya; Sri Mulyanti; Nadini Widya Hastuti; Dewi Fitria; Dhella Angelina Fitri; Yunita Wulandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study analyzes the integration of the Jambi folktale "Lebung Pendam" into performing arts at SDN 14/I Sungai Baung, Muara Bulian, Jambi. Employing a case study method and qualitative approach, it explores how the folktale is adapted into music and dance performed by students. To ensure data validity, source and method triangulation techniques are utilized by comparing interview results, observations, and documentation. The study encompasses a description of the "Lebung Pendam" folktale, the integration process into performing arts, implementation of activities at the school, and the positive impacts generated. The findings indicate that integrating folktales into performing arts can enhance students' appreciation of local culture, enrich their creativity, and strengthen cultural identity within the school environment.